Comprehensive review of Chromatographic, Hyphenated, and Spectrophotometric methods for the determination of Loxoprofen Sodium - Doifode, Sonika S.; Kulkarni, Rupesh (Drug Analytical Research, 2026)
Loxoprofen sodium, a propionic acid derivative and non-steroidal anti-inflammatory drug (NSAID), is widely prescribed for the management of pain, inflammation, and musculoskeletal disorders. As its therapeutic application expands, robust and precise analytical methods are essential to ensure the quality, safety, and efficacy of loxoprofen sodium in bulk drug substances, pharmaceutical formulations, and biological matrices. In recent years, significant progress has been made in the development and validation of analytical approaches, including UV spectrophotometry, RP-HPLC, HPTLC, and advanced UHPLC techniques. Optimization of chromatographic parameters, such as mobile phase composition, column selection, and detection wavelength, has enhanced sensitivity, resolution, and reproducibility. Method validation, in line with ICH guidelines, routinely evaluates accuracy, precision, linearity, specificity, and robustness to confirm reliability. Stability-indicating methods are particularly important for assessing degradation under stress conditions, providing insight into drug stability and shelf-life. Current analytical trends emphasize green and quality-by-design (QbD) approaches, supporting eco-friendly and efficient method development. Collectively, these analytical advancements establish a comprehensive framework for the routine quality control and research of loxoprofen sodium, reinforcing its clinical relevance and regulatory compliance.